Ovarian metastasis from lobular breast carcinoma: A case report with review of literature - Yasameen M. Mohammed; Zuhair D. Hammood; Abdulwahid M. Salih; Hadeel A. Yasseen; Soran H. Tahir; Sami S. Omar; Rebaz Haji Ali; Rawa M. Ali; Belan Mikaeil M. Radha; Ayman M. Mustafa; Fahmi H. Kakamad (Radiology Case Reports)
Although breast cancer can metastasize to various sites, involvement of the ovaries is infrequent. The current study aims to report a case of ovarian cancer originating from the breast along with an in-depth analysis of the literature. A 58-year-old woman with a history of invasive lobular carcinoma underwent surgery followed by adjuvant chemo-radiotherapy. During regular follow-up, a suspicious ovarian mass was detected, later confirmed to be metastasis from the breast cancer. A review of 25 studies on Google Scholar and PubMed identified 7185 ovarian metastasis patients, with 1253 cases originating from breast cancer, accounting for approximately 17.4% of all metastatic ovarian cancers. Bilateral ovarian involvement was noted in 75% of cases, with right-side involvement in 5.7% and left-side in 19.3%. Only 13 studies documented menopausal status, showing 53.6% were premenopausal. Controversies persist in distinguishing primary ovarian cancer from metastasis using clinical signs, serum markers, and imaging. Metastasis of breast cancer to the ovaries is an uncommon event, even after utilizing various therapeutic approaches. Surgery is the treatment of choice for these cases. This case highlights the importance of long-term surveillance in breast cancer patients and emphasizes the role of surgery in managing ovarian metastases.